1992
DOI: 10.4315/0362-028x-55.3.157
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Compounds Produced by a Chicken Intestinal Strain of Lactobacillus acidophilus

Abstract: The production of antagonistic compounds was studied with a strain of Lactobacillus acidophilus isolated from chicken intestinal tract. Accumulation of lactic acid (0.15 mol/l), hydrogen peroxide (280 nmol/h/mg cell dry weight), and a bacteriocin (ca. 10,000 arbitrary activity units per ml) was observed in cultures of this strain. In conditions eliminating the effects of organic acids and hydrogen peroxide, the bacteriocin, designated LA-147, showed inhibitory activity against strains of Lactobacillus leichman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…It is also suggested that adhesive probiotic bacteria could prevent the attachment of pathogens, such as pathogenic coliform bacteria and clostridia and stimulate their removal from the infected intestinal tract (Tamura et al 1983;Lidbeck et al 1987;Benno and Mitsuoka 1992;Saxelin et al 1995). They could inhibit pathogenic microbial growth by production of inhibitory compounds, such as organic acids, dihydrogen peroxide and bacteriocins (Juven et al 1992;Fazeli et al 2004Fazeli et al , 2006Walencka et al 2008). Adhesion of probiotic microorganisms to the intestinal mucosa is considered important for many of the observed probiotic health effects such as antagonistic activity against enteropathogens (Coconnier et al 1993a), modulation of immune system (Schiffrin et al 1997) and increased healing of damaged gastric mucosa (Elliot et al 1998).…”
Section: Cfumentioning
confidence: 93%
“…It is also suggested that adhesive probiotic bacteria could prevent the attachment of pathogens, such as pathogenic coliform bacteria and clostridia and stimulate their removal from the infected intestinal tract (Tamura et al 1983;Lidbeck et al 1987;Benno and Mitsuoka 1992;Saxelin et al 1995). They could inhibit pathogenic microbial growth by production of inhibitory compounds, such as organic acids, dihydrogen peroxide and bacteriocins (Juven et al 1992;Fazeli et al 2004Fazeli et al , 2006Walencka et al 2008). Adhesion of probiotic microorganisms to the intestinal mucosa is considered important for many of the observed probiotic health effects such as antagonistic activity against enteropathogens (Coconnier et al 1993a), modulation of immune system (Schiffrin et al 1997) and increased healing of damaged gastric mucosa (Elliot et al 1998).…”
Section: Cfumentioning
confidence: 93%
“…Although the mechanism of pathogen inhibition by lactic acid bacteria (LAB) is not completely understood, it is known that these microorganisms inhibit the adherence, multiplication and pathogenic action of invasive microorganisms (Saavedra 1995). The antagonistic mechanisms of LAB may include the activity of organic acids, hydrogen peroxide (Shahani and Chandan 1979;Juven et al 1992), diacetyl, bacteriocins and other compounds (Helander et al 1997). …”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows that of the solvents used, chloroform seems to be the best solvent in the extraction of antibacterial compound to prevent the growth of V. cholerae and S. pneumoniae whereas butanol was found to extract antibacterial compound efficiently to inhibit S. dysentriae. A control was tried where only solvent was Numerous to count Numerous to count added to the wells to see if solvent caused the inhibition but solvent alone without the antimicrobial compound had no effect on the organisms (Muriana and Klaenhammer, 1991;Juven et al, 1992;Peant and Lapointe, 2004).…”
Section: Discussionmentioning
confidence: 99%